2016
DOI: 10.1088/0953-4075/49/17/175501
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-small time-delay estimation via a weak measurement technique with post-selection

Abstract: Weak measurement is a novel technique for parameter estimation with higher precision. In this paper we develop a general theory for the parameter estimation based on weak measurement technique with arbitrary postselection. The previous weak value amplification model and the joint weak measurement model are two special cases in our theory. Applying the developed theory, the time-delay estimation is investigated in both theory and experiment. Experimental results shows that when the time-delay is ultra small, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Meanwhile, the pointer spectrum corresponding to different final system states are given by | ψ f k |ψ in | 2 ζ k (g, p)P 0 (p) with k = 1, 2, and we get [19]:…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the pointer spectrum corresponding to different final system states are given by | ψ f k |ψ in | 2 ζ k (g, p)P 0 (p) with k = 1, 2, and we get [19]:…”
Section: Theorymentioning
confidence: 99%
“…To demonstrate the DWVA approach, we study its application in ultra-small longitudinal phase change measurement. It has been shown that WVA technique is competent to this task [18,19,21,22,25], with sensitivity beyond attosecond (as) has been experimentally demonstrated [19]. In theory, BWVA can achieve sensitivity of 10 −5 as, however this prediction has not yet been demonstrated, partly due to its extremely low output signal intensity.…”
Section: Application In Longitudinal Phase Change Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…While the meaning of weak values has been debated since their inception [2][3][4][5], several experimental implementations of the weak measurement protocol have been carried out: weak values have thus been measured for different observables in many quantum systems [6][7][8][9][10][11][12][13]. Concurrently, theoretical schemes based on weak measurements have been proposed with practical [14][15][16] or foundational [17][18][19][20][21] aims.…”
Section: Introductionmentioning
confidence: 99%
“…It is composed by the information obtained from the measurement on the pointer state after the post-selection and the successful post-selection probability P d . The normalized probability distribution of x after the measurement on the pointer state is [20] P…”
Section: Adaptive Weak Value Amplificationmentioning
confidence: 99%